Which PSMA PET/CT interpretation criteria most effectively diagnose prostate cancer? a retrospective cohort study - Le Ma; Yaxin Hao; Luoping Zhai; Wanchun Zhang; Xiaoming Cao; Kaiyuan Jia (BMC Medical Imaging)
Abstract Background PSMA PET/CT emerges as a pivotal technology in the diagnostic landscape of prostate cancer (PCa). It offers a suite of imaging interpretation criteria, notably the maximum standardized uptake value (SUVmax), the molecular imaging prostate-specific membrane antigen score (miPSMA score), and the PSMA reporting and data system (PSMA-RADS). Identifying the most valuable criteria for diagnosing PCa and standardizing imaging interpretation across various tracers is an unresolved question. Our study endeavors to pinpoint the most optimal criteria to enhance the precision of PCa diagnosis, encompassing clinically significant PCa (csPCa), by evaluating the consistency and diagnostic accuracy of these three criteria using two [18F]-labeled PSMA tracers. Method This retrospective analysis spans a five-year period, focusing on patients with clinically suspected or newly diagnosed, treatment-naïve PCa who underwent 18F-PSMA PET/CT. The study is bifurcated into two segments: 1.A direct comparison assessing the consistency in SUVmax, miPSMA scores, and PSMA-RADS among PSMA PET/CT tracers ([18F]DCFPyL and [18F]PSMA-1007) for prostate foci in 24 patients. 2. An analysis of the diagnostic accuracy of these three criteria for both PCa and csPCa across 55 [18F]DCFPyL and 65 [18F]PSMA-1007 PET/CT scans, respectively. Results 1.Our head-to-head study reveals that SUVmax and miPSMA score exhibit near-perfect consistency, with PSMA-RADS demonstrating substantial consistency. 2. The diagnostic accuracy ranking, considering both PCa and csPCa, stands as miPSMA score ≈ SUVmax > PSMA-RADS for [18F]DCFPyL PET/CT, contrasting with miPSMA score > SUVmax ≈ PSMA-RADS for [18F]PSMA-1007 PET/CT. Conclusion The miPSMA score outperforms SUVmax and PSMA-RADS in terms of inter-tracer consistency and diagnostic accuracy for the detection of PCa, including csPCa, when comparing [18F]DCFPyL and [18F]PSMA-1007 PET/CT scans. This underscores the miPSMA score’s potential as a robust criterion for PCa and csPCa diagnosis, holding substantial promise for refining clinical decision-making and patient management strategies. Clinical trial number not applicable.